Clinical Profile and Etiology of Patients with Pericardial Effusion - Gupta, Madhu; Prasad, Maheshwar; Lal, Achutanand; Mishra, Jeetendra; Ali, Imran; Bhatta, Parash; Khadka, Salina (Journal of National Heart and Lung Society Nepal, 2023)
Background: Pericardial effusion are one of the common cardiac problems in our part of the world and is associated with high risk of morbidity and mortality if not diagnosed and treated. The aim of this study was to determine etiological spectrum and clinical presentation of moderate to large pericardial effusion. Methods: A descriptive cross-sectional study was conducted from February 2023 to July 2023 at Department of Cardiology, NMC-TH. Fifty patients were included in the study who visited to NMC-TH; OPD, ward and emergency department. Apart from routine investigations, ECG, chest X-ray and echocardiography were performed in all patients. Pericardiocentesis was done in 37 patients (74%). Specific investigations for the suspected etiological diagnosis were done. Results: A total of 50 patients (30 Male, 20 Female) were included in the study with age ranging from 11 to 76 years. The most common clinical presentations were dry cough (86%) followed by shortness of breath (70%) and fever (66%). In this study, the most common etiology of pericardial effusion was tuberculosis (n-22; 44%) followed by malignancy 6(12%), idiopathic 6(12%), and Hypothyroidism 4(8%). Among malignancies, carcinoma of lung was the commonest 3(50%). Tuberculosis was the most common cause in patients presenting with tamponade 8(61.5%) followed by malignancy 2(15.3%). Conclusion: This study shows tuberculosis is the most common cause of pericardial effusion followed by malignancy.